KUR’ÂN’DA GEÇEN FEME’STÂ‘Û ????? ?????????? İLE LEM TESTI‘ ???? ???????? ÜZERİNE [1-43] - Bayam, Abdulkadir (Fırat University, 2018)
Mekke döneminde Ğâşiye sûresinden sonra inen ve adını 9-26. âyetlerde yer alan Ashâb-ı Kehf kıssasındaki “mağara” anlamlı kehf kelimesinden alan Kehf sûresi, Kur’ân-ı Kerîm’in on sekizinci sûresidir. Bu sûrede Ashâb-ı Kehf kıssasına yer verildiği gibi 60-82. âyetlerde Hz. Mûsâ-Hızır kıssasına ve 83-101. âyetlerde de Zülkarneyn kıssasına yer verilmektedir. Son iki kıssada konumuz açısından büyük önem arz eden iki fiil geçmektedir. Kehf sûresini baştan sona okuyan bir kişi önce 78. âyette ???? ile meczûm ??????????? muzâri fiiliyle, sonra da 82. âyette yine ???? ile meczûm ????????? muzâri fiiliyle karşılaşır ve hayretler içinde kalır. 97. âyette önce ???ile olumsuzlanmış ??????????, sonra yine ??? ile olumsuzlanmış ???????????? mâzi fiilleriyle karşılaşınca bu hayreti ikiye katlanır. Zira ???’dan ??muzâri formunda birçok kez geçmekteyse de bu ilgili âyetlerde durum farklılık arz etmektedir. Bu âyetleri okuyan bir kişinin mezkûr fiillerde meydana gelen değişimi merak etmesi ve nedenlerini araştırması son derece doğaldır. İşte bu çalışmada 97. âyette yer alan ???????????????? ve 82. âyette yer alan ?????????? ???, yapı ve anlam yönünden etraflıca ele alınarak akla gelebilecek bazı sorulara cevaplar aranmaktadır

The Surah of al-Kahf descending from after al-Ghashiyah in the period of Mecca and taking its name from the word of al-kahf meaning “the cave” in the story of the People of the Cave located 9-26th verses is the eighteenth chapter of the Qur’an. In this surah, the story of Moses and al-Khidr has been found in 60-82nd verses and the story of Zul-Qarnain in 83-101 verses as well as the story of the People of the Cave. In the last two chapters, there are two verbs which are of great importance in terms of our topic. One who reads the Surah of al-Kahf from beginning to end is firstly encountered with ??????????? verb put into the apocopate form with ???? in 78th verse and then ????????? imperfect verb put into the apocopate form with ???? in 82nd verse and remains in astonishment. When he is encountered with the past tence verb of ?????????? negated with ??? in 97th verse and then the preterit verb of ????????????, his astonishment doubles. However, the verb being talked about, which is the ???????????? aspect from ??? has been repeated many times in the form of the past tence and especially imperfect verb, the situation is different in these related verses. It is perfectly natural for a person who reads these verses to inquire into the cause of the change in question and investigate the reasons. In this work, the answer to some questions coming to the mind are searched in the context of ???????????????? located in 97th verse and ????????????? found in the 82nd verse by approaching extensively in terms of structure and meaning
About ???????????????? And ????????????? In The Qur’an